Sistemas únicos, centralizados e integrados para a gestão de redes de franquias - Kalaf, Edison Audi (2009)
The chain business organization model, including the franchising system, is growing up faster then the economy average. The importance of franchising in Brazil as a supplier of products and services and its social significance by creating jobs and collecting taxes makes the franchising chains administration a very important issue, justifying all the efforts seeking for improvement in this area. The characteristics of this organizational model bring specific challenges to managers, mainly the integration of the chain components: franchisers, franchisees and chain customer. This dissertation has the following main objectives: to show why the use of heterogeneous and non-integrated systems by franchising chains can increase the management problems of these kind of organizations; to define an architecture of a unique, centralized and integrated system to franchising chains; and to propose its adoption by managers of franchising chains to mitigate or even eliminate several identified administration problems. The results of a research about the administration system adopted by educational franchising chains in Brazil are presented to evidence its integration stage. Finally, a case study shows the perception of the benefits followed by the adoption of a unique, centralized and integrated management system by an educational franchising chain. The research results show that a great number of educational franchising chains in Brazil still adopt heterogeneous and non-integrated systems on the chain units. This kind of solution makes the exchange of data, information and knowledge difficult, reducing the collaboration between the chain members and confusing the chain administration. This study proposes a systems architecture that ensures the integration between the chain elements, becoming an important management tool to educational franchising chains, facilitating the agility and increasing the competitive capacity for these organizations. This is the perception of the executive managers of the franchising chain case study that adopted a unique, centralized and integrated system and had an improved administration capacity